Perceptions of participation and the role of gender for the engagement in solar energy communities in Sweden - Daniela Lazoroska; Jenny Palm; Anna Bergek (Energy, Sustainability and Society, 2021)
Abstract Background Energy communities are emphasized by the EU as important for developing sustainable energy systems that include and engage many people. While many renewables are highly compatible with a more decentralized energy system, research indicates that participation in ‘desirable’ energy activities and energy decision-making is influenced by social and economic factors, including gender, economic status and home ownership. The overall aim of this article is to contribute to this line of inquiry by exploring how and under which conditions energy communities allow for broader participation in the energy system. This article examines how gender, as a more specific condition, influences the extent to which parties can or cannot engage with collective solar ownership models by means of a qualitative study of 11 solar energy communities and one housing association in Sweden. Results The study revealed that despite the relative potential for inclusion that they hold, energy communities can raise justice concerns in terms of inequities concerning access, capacity, and opportunity to engage in decision-making. Conclusions While solely focusing on gender offers a limited view of the dynamics of inclusion and exclusion in renewable energy projects, it is our position that integrating it into the analysis will provide insights into possible measures to remedy limitations and accelerate the renewable energy transition.